Low operational cost distributed prioritised coordinated control for DC microgrids. Issue 2 (29th March 2019) - Zaery, Mohamed; Ahmed, Emad M.; Orabi, Mohamed
Abstract : This study presents a distributed prioritised coordinated control topology that has the capability to reduce the total generation cost and maintain the average DC microgrid voltage. The main advantage of this topology over the addressed ones is developing a prioritised normalised running cost methodology. In this methodology, the best economical combination of DGs is selected to fulfil the load demand and maintain the minimum required spinning reserve power. The developed coordinated controllers contain tertiary and secondary levels cooperating to guarantee economical load sharing between the dispatchable DGs through precise adjustment of the primary voltage levels. Simulation and experimental results verify the efficacy and feasibility of the proposed dispatch scheme compared to the conventional power‐sharing techniques. In addition, system reliability enhancement during communication link failure and DG plug‐n‐play are investigated as well.